New Straita Times, 13 February 2009 - Hamidah Atan (The New Straits Times Press (M) Bhd, 2009)
Civil servants need to be more creative in implementing policies which should also become more people-friendly over time, Datuk Seri Abdullah Ahmad Badawi said yesterday.